Transformation of e-commerce Strategies under the Influence of Innovative Artificial Intelligence Solutions in the Digital Economy - Shynkarenko, Roman (Актуальні питання економічних наук, 2025)
The purpose of the study is to analyze the impact of artificial intelligence on e-commerce management strategies and develop recommendations for their adaptation to modern digital challenges. To achieve these objectives, the structural analysis of digital technologies, comparative study of business models, and evaluation of the effectiveness of artificial intelligence (hereinafter - AI) tools in interaction with consumers were used. The study reveals how AI is changing approaches to the development of e-commerce in the context of digital transformation. It is determined that the use of AI technologies contributes to the improvement of business processes, personalization of interaction with consumers and increase in the effectiveness of marketing strategies. Special attention is paid to the issues of adaptation of companies to rapid market changes caused by the active development of digital technologies. It is noted that the introduction of AI allows companies to respond quickly to market changes, increasing the accuracy of demand forecasting and optimizing pricing management. It is confirmed that the automation of customer interaction improves the level of service and contributes to strengthening customer loyalty. The practical significance of the results obtained is to formulate recommendations for the use of AI in e-commerce, which relate to improving marketing strategies, increasing the level of analytics of consumer expectations, and improving data security. The conclusions summarize that without a proper strategic approach, the use of AI can lead to excessive standardization of consumer experience, which will negatively affect the uniqueness of brands. The analysis made it possible to identify the main trends important for the formation of strategic decisions and patterns in the use of AI. Promising areas for further research include analyzing the long-term impact of AI on brand management, assessing the level of consumer confidence in automated services, and developing new mechanisms for protecting information in the digital environment. Additionally, it is important to investigate how AI technologies can adapt to the cultural characteristics of consumers in different regions, which affects the global strategies of companies.